Atividade nematicida in vitro da casca do fruto de Punica granatum L. Sobre helmintos gastrintestinais de caprinos - Felix, Renata Cristinne da Silva (Universidade Federal Rural do Semi-Árido, 2019)
Goat farming is considered an activity of great importance. However, there is difficulty in raising herds due to gastrointestinal parasites. The use of allopathic chemical compounds is the most common way to control these parasitoses; however, management errors in the use of these anthelmintics caused an increase in the cost of creation and development of parasitic resistance. With this, phytotherapy became a viable alternative in the treatment of gastrointestinal parasites, in which the species Punica granatum L. stands out, because it has antioxidant, antimicrobial and anti-inflammatory actions, but still with no proven antiparasitic effect. Thus, the objective of the study was to evaluate in vitro the ovicidal activity, to analyze the phytochemistry and the toxicity of the saline extract obtained from the peel of the P. granatum fruit. To do this, a total of five faecal samples were collected in a sample pool of 10 % of a goat herd, in which eggs were counted per gram of faeces to confirm the level of infection. Afterwards, the eggs were recovered for the development of the egg hatch test, the phytochemical analysis and the toxicity in Artemia salina using the saline extract of the pomegranate peel. The results showed that the extract had inhibitory activity on egg hatching, presenting 99 %, 99 %, 98 % and 95 % inhibition when used at 25 mg/mL, 12.5 mg/mL, 6.25 mg/mL and 3.12 mg/mL, respectively. In the phytochemical analysis, the presence of fenois, anthraquinones, condensed and hydrolysable tannins was verified, and these secondary metabolites could be related to the antiparasitic activity of the extract. In the toxicity test, P. granatum extract presented CL50 of 6.19 mg/mL. It is concluded that the extract tested shows ovicidal activity, several secondary metabolites and absence of toxicity in the lowest concentration tested in which it presented ovicidal action. Therefore, the extract obtained from the peel of the fruit of the pomegranate can be a viable alternative of treatment against the parasitoses that affect the small ruminants.
Monografia
Keywords: Parasitose; Pequeno ruminante; Resistência; Fitoterápico; Parasitosis; Small ruminant; Resistance; Phytotherapic; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA